PEMANFAATAN LIMBAH LUMPUR PD PAL SEBAGAI BAHAN PEMBUATAN PUPUK ORGANIK - Rijali Noor; Tri Cahyo Kurniawan (INFO-TEKNIK, 2014)
Sludge is mud that has particularly the potential use of a very large, PD PAL Banjarmasin manage sewage sludge simply by just piling them in one place. Sludge is a mud that can be processed into organic fertilizer because the sludge contains many microbial decomposer excellent for composting. This study uses sludge as main ingredients are mixed with other additives to be used as organic fertilizer.Composting method is to use the results of an open windrow composting will be tested maturation of the content of N, P, K, the value of C-Organic and C / N ratio and will be compared with SNI 19-7030-2004. The variations include 5 variations with 3 repetitions.Based on the composting time, the most precocious variation is variation of A (without activator) and Variation C (with the addition of Trichoderma sp.) Which for 19 days while the longest is the variation of D (with the addition dectro), while based on the temperature, variations can reaching the highest temperature is in the variation of C (with the addition of Trichoderma sp.) for the content of N, P, K, the value of C-Organic and C / N ratio of all variations still meet the requirements of SNI 19-7030-2004. Of N, P, K, organic-C test and ANOVA using SPSS DMRT test for values of N are the most significant and real different is the variation of B (with EM-4), for which the most significant element of P and E were significantly different in variation (Control), element K is the most significant and significant differences in the variation of B (with EM-4), the value of organic C of the most significant and significant differences in the variation of C (with Trichoderma sp.) and C / N ratio of the most significant and significant differences in the variation of A (without activator) is the best fertilizer variation in terms of the speed of composting and nutrient content is the variation of C with the addition of Trichoderma sp. Keywords: EM-4, Trichoderma sp., Dectro, sewerage, Organic Fertilizer.